2022
DOI: 10.3390/su14095126
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors at Different Canopy Heights Had Significant Effects on Leaf Water-Use Efficiency in Cold-Temperate Larch Forest

Abstract: It is of great significance to study short-term water-use efficiency (WUEs) at different canopy heights for accurately evaluating the adaptability of cold-temperate larch (Larix gmelinii) forest to climate change. The stable isotope method combining data of gradient meteorology, photosynthetic properties and leaf structure were used to assess the influence of different canopy heights on short-term water-use efficiency (WUEs) in larch forests in the northern Da Hinggan Mountains. The results show that: (1) The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…SLA can reflect the differences of leaf anatomical structure that can influence the variability of iWUE between species via changes in mesophyll conductance (Mediavilla et al 2001;Tomás et al 2013;Carriquí et al 2015;Trueba et al 2021). Previous studies reported that SLA was negatively correlated with iWUE and δ 13 C in crops (Craufurd et al 1999;Reddy et al 2020a,b), shrubs (Horike et al 2023) and trees (Wang et al 2013;Ge et al 2022;Zhong et al 2023). Our results also show the tendency of a negative correlation between SLA and both iWUE and δ 13 C, though this was significant only for the relationship with δ 13 C of juvenile species inter-specifically and with the iWUE of mature trees intra-specifically.…”
Section: Specific Leaf Area and Water-use Efficiencymentioning
confidence: 92%
See 1 more Smart Citation
“…SLA can reflect the differences of leaf anatomical structure that can influence the variability of iWUE between species via changes in mesophyll conductance (Mediavilla et al 2001;Tomás et al 2013;Carriquí et al 2015;Trueba et al 2021). Previous studies reported that SLA was negatively correlated with iWUE and δ 13 C in crops (Craufurd et al 1999;Reddy et al 2020a,b), shrubs (Horike et al 2023) and trees (Wang et al 2013;Ge et al 2022;Zhong et al 2023). Our results also show the tendency of a negative correlation between SLA and both iWUE and δ 13 C, though this was significant only for the relationship with δ 13 C of juvenile species inter-specifically and with the iWUE of mature trees intra-specifically.…”
Section: Specific Leaf Area and Water-use Efficiencymentioning
confidence: 92%
“…SLA decreases in plants with thicker leaves (Vile et al 2005;Homeier et al 2021). Multiple studies have found that SLA is negatively related to iWUE and δ 13 C in crops (Reddy et al 2020a;Reddy et al 2020b), shrubs (Horike et al 2021) and tree species (Ge et al 2022). The correlation between SLA and iWUE might be caused by anatomical differences that affect the mesophyll tissue surface area and mesophyll conductance (Baird et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A study by Medrano et al (2009) also reported a positive correlation between WUE i and LMA in Mediterranean herbs and shrubs. Similarly, LMA was positively correlated with WUE 13C among trees ( Betula, Larix, Pinus ) in the boreal forest ( Ge et al 2022 ). A thicker leaf can be associated with a thicker boundary layer, which lowers transpiratory losses and ultimately improves WUE bio ( Bramley et al 2013 ).…”
Section: Leaf Anatomy and Plant Crown Architecturementioning
confidence: 93%